2016
DOI: 10.1186/s40945-016-0016-2
|View full text |Cite|
|
Sign up to set email alerts
|

Physical fitness of Ghanaian physiotherapists and its correlation with age and exercise engagement: a pilot study

Abstract: BackgroundThe physical job demands of physiotherapists require optimal level of physical fitness (PF), which is often not evaluated in practice. In this study, we assessed selected components of physical fitness of Ghanaian physiotherapists in relation to their sex, age and frequency of exercise participation.MethodsPhysiotherapists practicing in four major hospitals within the Accra Metropolis of Ghana were enrolled into this cross-sectional survey. Three major components of physical fitness (flexibility, car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Consequently, students should be directed to perform activities that will increase the extensibility of the dorsal muscle chain of the boot and hip ( 40 ). Again, a similar result was observed in another study ( 41 ).…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, students should be directed to perform activities that will increase the extensibility of the dorsal muscle chain of the boot and hip ( 40 ). Again, a similar result was observed in another study ( 41 ).…”
Section: Discussionsupporting
confidence: 91%
“…According to the established norms [8], THCC had a good level of flexibility in both male and female subjects. In Bello et al [3] study, the flexibility of physiotherapy students was observed as "lower than average", while the results of Boraczyński et al [5] showed an excellent level of flexibility among physiotherapy students. Compared to THCC and KCAS subjects of both genders, the KCAS subjects' flexibility also corresponds to the level of "good" and no statistical difference was observed between the subjects of the higher education institutions.…”
Section: Discussionmentioning
confidence: 92%
“…Physical therapy (PT) students, due to their nature of work, must have better CRF and overall health, but reports of low fitness in PT students and lack of emphasis on these topics at the entry-level PT curriculum have been noticed 15 . CVD, being the number one cause of death worldwide, refers to any disease that affects the cardiovascular system 16 .…”
Section: P R O V I S I O N a L L Y A C C E P T E D F O R P U B L I C A T I O Nmentioning
confidence: 99%